Implementasi Pendidikan Karakter dalam Mengatasi Krisis Moral di Sekolah Dasar - Zuliani, Rizki; Apriliyani, Dewi; Kurnia, Lisa (Lembaga Yasin AlSys, 2023)
Character education is a system of cultivating character values which includes components of knowledge, feelings, and actions as a form of moral development and individual behavior. The lack of character education will lead to a moral crisis that will have a negative impact on society. This study uses a qualitative descriptive approach to the type of library research. The data collection technique is by collecting data and related sources from books, written materials and references that are relevant to the research being carried out. The result of this study is that providing moral education for students can change the behavior of students, so that when they are adults they have responsibility, respect each other, and are able to face the challenges of the rapidly changing times. The development of the times, family, peers, school environment, and social environment also have a major impact on students' moral damage so that character education can be a solution to these problems.